Restructuring the Pancasila-Based Representative Democracy System Through Formulations of Political Education by Political Parties - Mahanani, Anajeng Esri Edhi; Anggriawan, Teddy Prima (Law Research Review Quarterly, 2018)
The existence of political parties, especially in Indonesia, one of which is aimed at maximizing the function of political education both for the general public and for political party cadres, as the Explanation of Law Number 2 of 2011 concerning Amendments to Law Number 2 of 2008 concerning Political Parties. This study aims to restructure or realign the objectives of the Indonesian state democracy, by reviewing the principle of representative of the people. Research begins by examining the concept of representative democracy in accordance with the values ​​of Pancasila, which is then used as a reference to formulate political education by political parties. This formulation of Pancasila-based political education is the object of research in this paper, which was analyzed by using the normative method assisted by literature study. Based on the discussion, it can be said; First, democracy on the basis of Pancasila is a representative democracy, create the representatives of the people who should not only be interpreted as "assistants" as a result of the degradation of constituent trust in the people's representatives. Contrary, representative democracy is not interpreted as an absolute or fully representative democracy, which in practice actually encourages constituent apathy and then supports the practice of a semi-timocratic system with the appearance of democracy. Second, the formulation of political education must be restructured in the spirit of Pancasila values, especially through the alignment of understanding of representative democratic systems as recommendations for political parties to carry out political education functions.